Selective Vulnerability of the Locus Coeruleus Noradrenergic System and its Role in Modulation of Neuroinflammation, Cognition, and Neurodegeneration - Evans, Andrew K.; Defensor, Erwin; Shamloo, Mehrdad (Frontiers in Pharmacology, 2022)
Locus coeruleus (LC) noradrenergic (NE) neurons supply the main adrenergic input to the forebrain. NE is a dual modulator of cognition and neuroinflammation. NE neurons of the LC are particularly vulnerable to degeneration both with normal aging and in neurodegenerative disorders. Consequences of this vulnerability can be observed in both cognitive impairment and chronic neuroinflammation. LC NE neurons are pacemaker neurons that are active during waking and arousal and are responsive to stressor in the environment. Chronic overactivation is thought to be a major contributor to vulnerability of these neurons. Here we review what is known about mechanisms underlying this neuronal vulnerability and combinations of environmental and genetic factors that combine to confer risk to these important brainstem neuromodulatory and immunomodulatory neurons. Finally we discuss an array of potential interventions that may reduce overall risk for LC NE neuronal degeneration.